The Role of Leadership and Motivation on Employee Performance: PT. Multi Media Kabar Case Study - Malalantang, Drevy (Open Access Indonesia Journal of Social Sciences, 2023)
This research aims to determine the influence of leadership and motivation on employee performance at PT. Multi Media Kabar. This type of research is quantitative. The data sources used in this research are direct observation and filling out questionnaires by employee respondents of PT. Multi Media Kabar. This research uses multiple regression analysis. The research results show that leadership and motivation partially have a significant positive effect on employee performance at PT. Multi Media Kabar. The analysis results through calculating the correlation coefficient (R) show a solid positive relationship between leadership and motivation factors and employee performance variables (Y). The results of the analysis through calculating the coefficient of determination (R2) show that leadership and motivation factors have a reasonably significant contribution or contribution to the variation (up and down) of employee performance (Y), in addition to the variation explained by other factors.